The impact of Levamisole on Newcastle disease antibodies titer in broilers fed with diet contaminated with Aflatoxin - AL- Naemey, Hatem M. M. (The Iraqi Journal of Veterinary Medicine, 2006)
This study designed to know the immuno suppressor effect of aflatoxinsand the efficacy of levamisole to reduce these effects in the titer of antibodiesand protection against challenge for Newcastle disease vaccine in chickens.This trail include three groups, first group fed on ration free fromaflatoxins contamination, Second group fed on ration contaminated withaflatoxins, while the third group fed on the same ration of second group andgiven levamisole via drinking water with the dose of 10mg/kg of body weight.All groups vaccinated twice against Newcastle disease at 10 and 20 daysof age. The immunity evaluated by ELISA test at 6, 19, 31 days of age andchallenged at 32 days old.The results indicate that the second group has the lowest titer ofantibodies and protection ratio after challenge, while the first group has thehightest titer of antibodies and high protection ratio after challenge. The titer ofantibodies and the protection against challenge in the third group had higher titerthan them at second group and lower than them at first group.These results revealed the role of aflatoxins in immunosuppression forNewcastle vaccines and reduce the efficacy of vaccination process and reducethe protection ratio after challenge, also reveal the role of levamisole in reducingof these effect and elevation of immune response to Newcastle vaccine inchickens.